Detectable minimal residual disease before allogeneic hematopoietic stem cell transplantation predicts extremely poor prognosis in children with acute lymphoblastic leukemia - Sramkova, Lucie; Muzikova, Katerina; Fronkova, Eva; Krejci, Ondrej; Sedlacek, Petr; Formankova, Renata; Mejstrikova, Ester; Stary, Jan; Trka, Jan (Pediatric blood & cancer, 2007)
BACKGROUND: The level of minimal residual disease (MRD) prior to allogeneic hematopoietic stem cell transplantation (HSCT) has been shown to be an independent prognostic factor for outcome of pediatric patients with high-risk acute lymphoblastic leukemia (ALL). Retrospective studies which used (semi-) quantitation of clone-specific immunoglobulin/T-cell receptor (Ig/TCR) rearrangements have documented the feasibility and practicality of this technique. This approach has also been disputed due to the occurrence of clonal evolution and generally high MRD levels prior to HSCT. PROCEDURE: In our prospective study, MRD before and after HSCT was monitored using quantitative real-time PCR in a cohort of 36 children with ALL consecutively transplanted in our center between VIII/2000 and VII/2004. RESULTS: In 25 of 36 patients, MRD level prior HSCT was assessed. Seventeen patients were classified as MRD-negative and eight were MRD-positive up to 9 x 10(-2). In MRD-positive subgroup, seven events (six relapses) occurred post-transplant in striking contrast to only one relapse in MRD-negative subgroup (event-free survival (EFS) log-rank P < 0.0001). MRD proved to be the only significant prognostic factor in a multivariate analysis (P < 0.0001). Adoptive immunotherapy including donor lymphocyte infusions in patients with adverse dynamics of MRD after HSCT had only limited and/or temporary effect. Clonal evolution did not present a problem precluding MRD monitoring in any of patients suffering a post-transplant relapse. CONCLUSIONS: We show that MRD quantitation using clonal Ig/TCR rearrangements successfully assesses the risk in pediatric ALL patients undergoing allogeneic HSCT. As our ability to treat detectable MRD levels after HSCT is very limited, alternative strategies for MRD-positive patients prior HSCT are necessary.
Keywords: polymerázová řetězová reakce; monitorování fyziologických funkcí; následné studie; lidé; mladiství; výsledek terapie; genová přestavba T-lymfocytů; Recurrence; Gene Rearrangement, T-Lymphocyte; Risk Factors; imunoterapie adoptivní; genová přestavba B-lymfocytů; Infant; Female; dítě; Gene Rearrangement, B-Lymphocyte; retrospektivní studie; Adolescent; Humans; Predictive Value of Tests; Follow-Up Studies; Polymerase Chain Reaction; Neoplasm, Residual; Lymphocyte Transfusion; reziduální nádor; recidiva; Hematopoietic Stem Cell Transplantation; akutní lymfatická leukemie; předškolní dítě; rizikové faktory; Monitoring, Physiologic; Child, Preschool; přežití bez známek nemoci; mužské pohlaví; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Transplantation, Homologous; transplantace hematopoetických kmenových buněk; Disease-Free Survival; ženské pohlaví; Immunotherapy, Adoptive; Treatment Outcome; Male; homologní transplantace; Retrospective Studies; Child; transfuze lymfocytů; prediktivní hodnota testů; kojenec